Ketimpangan Sosial dan Marginalisasi Tokoh dalam Cerpen "Laki-Laki yang Kawin dengan Peri" Karya Kuntowijoyo: Kajian Marxis - Aulia Syahfitri; Bertiana Putri Saragih; Natal Fransiska Manalu; Devi Enzelina Nainggolan; Elisabeth Siska Limbong; Sherly Ramadani (Jurnal Keluarga Sehat Sejahtera, 2026)
This article examines social inequality and the marginalization of characters in Kuntowijoyo’s short story “Laki-Laki yang Kawin dengan Peri” using a Marxist analysis. The study aims to describe the forms of social inequality, the process of marginalization, and the power relations experienced by the main character, Pak Kromo. The method used is qualitative descriptive analysis employing a literary sociology approach and Marxist theory. The data consists of excerpts from the short story that illustrate social domination, discrimination, and oppression. The results indicate that Pak Kromo faces social exclusion due to societal stigma, which creates an unjust social structure through stereotypes and rejection. The Marxist analysis reveals the conflict between dominant and oppressed groups that gives rise to social injustice. This short story also serves as a critique of a society that prioritizes stigma and collective power over humanistic values.